Population pharmacokinetic/pharmacodynamic modeling for remimazolam in the induction and maintenance of general anesthesia in healthy subjects and in surgical subjects - Zhou, Jie; Leonowens, Cathrine; Ivaturi, Vijay D.; Lohmer, Lauren L.; Curd, Laura; Ossig, Joachim; Schippers, Frank; Petersen, Karl-Uwe; Stoehr, Thomas; Schmith, Virginia (Journal of clinical anesthesia, 2020)
To evaluate factors affecting variability in response to remimazolam in general anesthesia. Plasma concentration-time data from 11 Phase 1–3 clinical trials were pooled for the population pharmacokinetic (popPK) analysis and concentration-bispectral index (BIS) data were pooled from 8 trials for popPK-PD analysis. A 3-compartment model with allometric exponents on clearance and volume described remimazolam concentrations over time. An effect compartment model with an inhibitory sigmoid Emax model was fit to the concentration-BIS data. Simulations were performed to assess sedation in general anesthesia and post-surgical sedation in healthy and sensitive populations. General anesthesia and post-surgical sedation. 689 subjects included in popPK and 604 subjects included in popPK-PD. Most subjects (>85%) were ASA Class 1 or 2, with the remaining subjects being ASA Class 3. Serial plasma concentrations and BIS scores. Standard intra-operative monitoring. PopPK model included an effect of extracorporeal circulation, ASA class, and sex on PK and a time-dependent clearance (~30% lower at 24 h) that was not related to cumulative dose. Co-administered remifentanil had a synergistic decrease in BIS with remimazolam. Remimazolam IC50 increased with cumulative dose. Onset was faster in overweight subjects and slower in Asian subjects. If using a weight-based regimen, simulations showed that remimazolam 6 mg/kg/h until loss of consciousness followed by 1 mg/kg/h during general anesthesia and 0.25 mg/kg/h for post-surgical sedation for up to 24 h is optimal, regardless of ASA class or sensitivity of subjects. If using a weight-based regimen, results illustrated an appropriate regimen of remimazolam for general anesthesia and post-surgical sedation in general and sensitive populations, although lower doses can be considered in elderly patients with a significant disease burden or in ASA Class 3 patients. The time-dependent change in clearance is not clinically relevant for up to 24 h. •PK-PD used to find remimazolam dose in general anesthesia for weight-based regimen.•Most covariate effects were small and did not change the dosing recommendations.•No dose adjustments required; but consider dose reduction in medically complex elderly patients.•Consider dose reduction in ASA Class 3 patients with significant disease burden.